Tissue damage-tracking control system for image-guided photothermal therapy of cancer - Céspedes Tenorio, Mauricio; Wattson Sánchez, Carlos A.; Dumani, Diego S. (Frontiers in Thermal Engineering, 2022)
Photothermal therapy (PTT) is a type of cancer treatment capable of damaging tumors using laser irradiation. This procedure can be a promising approach to complement current cancer therapies, due in part to its minimal invasiveness. One of the challenges of photothermal therapy is the potential collateral damage to the surrounding healthy tissue, as well as excessive temperature increase in the target tumor region that can cause tissue carbonization and evaporation. With the aim of increasing the performance of photothermal therapy in damaging targeted tumor while keeping healthy nearby tissue unaffected, this research proposes the use of a feedback control system that considers the cumulative thermal damage to both types of tissue. Two separate control algorithms (fuzzy logic and PI) were designed and tested in silico using simulations made in MATLAB® and Python. Results showed that both controllers successfully accomplished the proposed goals. Therefore, the feasibility of using these automated systems to improve the efficacy and safety of PTT was demonstrated.